Optimization of fractional order PID controllers based on genetic algorithms - Jun-Yi Cao; Jin Liang; Bing-Gang Cao (2005 International Conference on Machine Learning and Cybernetics, 2005)
The intelligent optimization method for designing fractional order PI/sup /spl lambda//D/sup /spl delta// controller (FOPID) based on genetic algorithms is presented in this paper. Fractional calculus can provide new and good performance extension for FOPID because of the arbitrary order of fractional calculus. However, the difficulties of designing FOPID controllers increase. FOPID controllers' parameters are composed of proportional constant, integral constant, derivative constant, derivative order and integral order, whose design is more complex than that of conventional integer order PID controller. The optimization design process based on genetic algorithms is analyzed in detail in this paper, in which the optimization performance target is the combination of ITAE and control input, the numerical simulation of FOPID controllers uses the method of Tustin operator and continuous fraction expansion. Simulation results show the proposed method is highly effective.